The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.eucr.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Fragmented Ureteral Stent Extraction: Flexible Renoscopy

Abstract: Usage of ureteral DJ stent is very common in urology practise. There are some complications according to the increased usage of ureteral DJ stent in the literature. Stent fragmentation is a rare complication of ureteral DJ stent. In this study we present a 53-year-old male patient who had previous stone surgery and a ureteral DJ stent applied to our polyclinic with complaint of 3-months-long right side pain. In the radiologic examination we observed that DJ stent was fragmented from the upper end on the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Stent fracture usually occur along stent side holes, so stents with multiple side holes are susceptible for fracture 4 management of fractured stents depends on where the fragments retained, can be managed by retrograde approach using ureteroscope or antegrade approach using nephroscope or combined retrograde and antegrade approach the same management which is used in our case 5 …”
Section: Discussionmentioning
confidence: 94%
“…Stent fracture usually occur along stent side holes, so stents with multiple side holes are susceptible for fracture 4 management of fractured stents depends on where the fragments retained, can be managed by retrograde approach using ureteroscope or antegrade approach using nephroscope or combined retrograde and antegrade approach the same management which is used in our case 5 …”
Section: Discussionmentioning
confidence: 94%
“…In this study, we report for the first time on SSF, which occurred as early as 3 weeks following stent insertion. SSF is a very rare complication 4‐6,9 . Regardless of the exact cause of stent fragmentation, both in vivo and in vitro reports have indicated that stents are more likely to fragment across the side drainage holes 2,13 …”
Section: Discussionmentioning
confidence: 99%
“…Aging of the stent has also been recognized as an important cause for stent fragmentation 10,14 . In this regard, reviewing the literature indicated that SSF had occurred in stents which have been neglected or forgotten for long periods ranging between one year to as long as 15 years which led to stent encrustations and crystal formation 4‐6,9 . There was only one report of SSF which occurred after two months of insertion 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations